Early spring flora of the Sub-Pannonic steppic grassland (NATURA 2000 site) in Bilje, northeast Croatia - Zuna Pfeiffer, Tanja; Spoljaric Maronic, Dubravka; Zahirovic, Vanda; Stevic, Filip; Zjalic, Milorad; Kajan, Katarina; Ozimec, Sinisa; Mihaljevic, Melita (Acta Botanica Croatica, 2016)
The diversity of early spring vascular flora was studied in the Sub- pannonic steppic grassland in the village of Bilje, north eastern Croatia. In all, 109 plant taxa within 35 families were found. The highest number of taxa belongs to the families Poaceae, Fabaceae, Asteraceae, Caryophyllaceae, Lamiaceae and Rosaceae. Specific habitat conditions, characterized by moderately wet and moderately acidic soil with intermediate fertility and the effects of the continental climate favour the development of different plant life forms. Out of the total recorded plant taxa, hemicryptophytes make up 59.6%, followed by therophytes (22.0%) and geophytes (13.8%). Chorological analysis shows that the most numerous are plants of Eurasian (33.9%), Pontic-Central-Asian (21.1%) and Central European (21.1%) floral elements. According to their status in the Red List, three critically endangered (CR), one vulnerable (VU) and three nearly threatened (NT) plant species were found. Altogether, the steppe-like grassland in Bilje is a unique habitat rich in valuable plants of the Croatian flora, including the critically endangered Doronicum hungaricum, therefore it is of great importance to preserve it. Important management tools include mowing and controlling the spreading of cultivated and invasive plant species.